Ocean acidification in the Western Pacific: Boron isotopic composition recorded in a tropical massive coral core from Lanyu Islet SE Taiwan - You, Chen-Feng; Lin, P-Y.; Huang, Kuo-Fang; Chung, Chuan-Hsiung; Liu, Zhifei (Frontiers in Marine Science, 2022)
Boron (B) and B isotopic compositions (δ11B) in biogenic carbonates are useful proxy for pH reconstruction in the ocean. However, high-resolution archives are scarce due to associated sampling and analytical difficulty. In this study, a well study core of modern long-lived massive coral skeletons (Porites lobata) from Lan-Yu Islet offshore southeastern Taiwan was drilled and used for high-resolution major/trace elements, B and δ11B, as well as O and C isotopes, analyses to investigate environmental changes during 1991-1997. The coralline results show a clear temporal trend in metal/Ca based sea surface temperatures (SSTs) in annual and monthly scale. In particular, the Mg/Ca-SSTs, the most sensitive temperature proxy at the study site, show a significant warming trend (+0.2 ℃/yr-1) during the study period. On the other hand, subtle annual δ11B changes was identified, corresponding to~0.2 pH, which is comparable with other coral records in Pacific, e.g., SCS, Guam Island, Flinders and Arlington Reef, as well as the in situ seawater pH measurement in Hawaii station. This corresponds to an acidification rate of~0.25 pH /100 yrs, similar as other coralline data, in situ pH /pCO2 measurement or prediction results. These observations emphasize the importance of ocean acidification due to anthropogenic activities. Combined with the Mg/Ca-SST, the intra-annual data show a clear seasonal cycle with higher pH in winter, consistent with pCO2 observations at the surface ocean. The chemical and isotopic results in corals conclude that biogenic carbonates are informative for pH reconstruction and contribute new insights on the relationships between climatic changes and potential biological responses in western Pacific.